The prevelance of female athlete triad among intervarsity team sport athletes / Saidatul Nur Fatihah Mohamed Sabadri - Mohamed Sabadri, Saidatul Nur Fatihah (Faculty of Sport Science and Recreation, 2016)
This cross sectional study conducted to determine the relationship between risk of female athlete triad and selected team sport during intervarsity sport competition. A total of 170 female athlete which consist of netball (n=32), softball (n=29), futsal (n=55) and handball (n=52) completed LEAF questionnaire. Pearson Chi Square were used to determine the association of female athlete triad risk with selected team sport. A significant association observed between risks of female athlete triad with selected team sport (X2=32.61, d:f=3, p<O.OOI). Therefore the athlete who involve in intervarsity sport competition had risk of having female athlete triad symptoms